Preoperative Metastatic Brain Tumor-Associated Intracerebral Hemorrhage Is Associated With Dismal Prognosis - Hamed, Motaz; Schäfer, Niklas; Bode, Christian; Borger, Valeri; Potthoff, Anna-Laura; Eichhorn, Lars; Giordano, Frank A.; Güresir, Erdem; Heimann, Muriel; Ko, Yon-Dschun; Landsberg, Jennifer; Lehmann, Felix; et al. (Frontiers in Oncology, 2021)
Object: Intra-tumoral hemorrhage is considered an imaging characteristic of advanced cancer disease. However, data on the influence of intra-tumoral hemorrhage in patients with brain metastases (BM) remains scarce. We aimed at investigating patients with BM who underwent neurosurgical resection of the metastatic lesion for a potential impact of preoperative hemorrhagic transformation on overall survival (OS). Methods: Between 2013 and 2018, 357 patients with BM were surgically treated at the authors’ neuro-oncological center. Preoperative magnetic resonance imaging (MRI) examinations were assessed for the occurrence of malignant hemorrhagic transformation. Results: 122 of 375 patients (34%) with BM revealed preoperative intra-tumoral hemorrhage. Patients with hemorrhagic transformed BM exhibited a median OS of 5 months compared to 12 months for patients without intra-tumoral hemorrhage. Multivariate analysis revealed preoperative hemorrhagic transformation as an independent and significant predictor for worsened OS. Conclusions: The present study identifies preoperative intra-tumoral hemorrhage as an indicator variable for poor prognosis in patients with BM undergoing neurosurgical treatment.